The effects of interest rate on loan repayment in Microfinance Institutions in Gweru - Mazingaizo, Shannon (Midlands State University, 2018)
The purpose of this study was to investigate the impact of interest rates on loan repayment in MFIs situated in Gweru. In this harsh economy evidenced in Zimbabwe where NPL continues to be the talk of the day as some clients fails to service their debts due to various factors . Theoretical and empirical literatures were both reviewed on loan repayment so as to make derivations and give the basis for a strong analysis. Studies carried out in other countries were integrated in the empirical literature review and various theories were used to give a theoretical assumption for this study. An explanatory research design was used to measure the strength of relationships between interest rates and loan repayment. A model was adopted from existing literature and essential adjustments were made to suit the properties of the study. A sample of 25 MFIs was drawn and a minimum of two questionnaires were administered per every institution. The conclusions of the study indicate that interest rates, sex and repayment period are significant determinants of loan repayment among other factors. Through the use of a logistic model, the author provides a model to be used in determining loan repayment. The study recommends that there is need to continuously keep interest rates on check as exorbitant interest charges are detrimental effects on loan repayment which will translates to a problem in the financial sector as whole. Also various loan facilities tailor made for female borrowers needs to be increased as they contain higher repayment capabilities as compared to their male counterparts.